2014
DOI: 10.1007/s11356-014-4000-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, quantification, and typing of human adenoviruses detected in river water in Taiwan

Abstract: The prevalence of human adenoviruses (HAdV) in river waters was investigated in this study. Water samples were collected from 13 rivers in Taiwan, concentrated, and assessed for the presence of HAdVs using nested polymerase chain reaction (PCR). Human AdV positive samples were then subjected to real-time PCR (qPCR) to quantify the viral genomes and further subjected to primer-based genotyping to identify the various serotypes present. For each water sample, several water quality parameters were evaluated, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 44 publications
1
11
1
Order By: Relevance
“…To our knowledge this constitutes the first report of NoV GII.P17 identification in water environments in Mexico. And, although HAdV 41 is reported to be the most prevalent serotype in other locales (Huang et al 2015;Tao et al 2016), the results reported here showed that serotype 40 was most prevalent in the YP karst aquifer, even though serotypes 40 and 41 were detected among the water samples tested.…”
Section: Sadv -18contrasting
confidence: 75%
“…To our knowledge this constitutes the first report of NoV GII.P17 identification in water environments in Mexico. And, although HAdV 41 is reported to be the most prevalent serotype in other locales (Huang et al 2015;Tao et al 2016), the results reported here showed that serotype 40 was most prevalent in the YP karst aquifer, even though serotypes 40 and 41 were detected among the water samples tested.…”
Section: Sadv -18contrasting
confidence: 75%
“…A previous study reported that the average viral loads of HuNoV was 2.30 log 10 genome copies/L in a river in the Netherlands [ 59 ]. Similarly, the viral load of AdenoV ranged from 2.79 to 2.93 log 10 genome copies/L in a river in Taiwan [ 60 ]. Furthermore, RotaV concentrations were as high as 4.14 log 10 genome copies/L in surface river water in Germany [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…To enhance virus recovery from the samples, the water samples were concentrated before analysis. Water samples (1 L) were vacuum‐filtered through a 42 mm GN‐6 membrane with a pore size of 0.45 μm (GN‐Metricel PALL) (Huang et al., 2015 ). Next, the filter paper was placed in 45 mL of phosphate‐buffered saline (PBS, pH 7.2) and kneaded for 5 min with sterile gloves.…”
Section: Methodsmentioning
confidence: 99%